2020
DOI: 10.51791/njap.v47i4.81
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth traits in three strains of broiler chicken

Abstract: This study was carried out to evaluate the growth performance of Marshall, Cobb and Arbor acre strains of broiler chicken. A total number of three hundred (300) day-old broiler chicks of Arbor acre, Cobb and Marshall strains were raised under the same management condition. Data was obtained on the growth performance and analyzed. Cobb strain had the highest weight of 175.78 ± 2.51g at 2 weeks of age while Arbor acre and Marshall strain had similar (p>0.05) body weight at that age. Marshall had the highest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
2
1
Order By: Relevance
“…This suggests that the diet did not alter any of the organ part in all the treatment groups. In contrast to the present study, the internal organs of Marshall, Arbor Acre and Cobb broilers as reported by Fadare et al (2020) showed significant (P<0.05) broiler strain effect on the weights of lung, liver, full gizzard, empty gizzard. The highest weight and relative percentage of lung was found in Marshall strain while Cobb and Arbor acre strains had similar lung weight and relative percentage.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This suggests that the diet did not alter any of the organ part in all the treatment groups. In contrast to the present study, the internal organs of Marshall, Arbor Acre and Cobb broilers as reported by Fadare et al (2020) showed significant (P<0.05) broiler strain effect on the weights of lung, liver, full gizzard, empty gizzard. The highest weight and relative percentage of lung was found in Marshall strain while Cobb and Arbor acre strains had similar lung weight and relative percentage.…”
Section: Discussioncontrasting
confidence: 99%
“…The result obtained in this work are in line with the report of Fadare et al (2020) who discovered that Marshall strain had the highest pre-slaughter weight (2215.00±18.50g) followed by cobb (2048.88 ± 10.30 g) while the least pre-slaughter weight was recorded in Arbor acre strain (1937.50 ± 12.40 g). Marshall strain also had the highest slaughter weight of 2130.00±15.25g while the least value of 1937.50±12.40g were recorded in Arbor acre strain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this present study, there were no significant (P>0.05) differences for dressing percentage, wings, chest, gizzard, lungs, spleen and kidney between the Cobb and Arbor acre strains. Non-significant differences in dressing percentage contradicted reports of Fadare, et al [18] for broiler strains.…”
Section: Effect Of Strain On Carcass Characteristics Of Birds Fed Exp...mentioning
confidence: 56%
“…However, there are diverse reports on the supremacy of the most familiar strains of broilers with particular reference to their carcass traits. Reports Fadare, et al [18] indicates a significant difference in dressing yield of Cobb and Arbor acre broiler strains. It was revealed that Cobb strain produced significantly higher mean dressing percentage (77.19±3.79%) than Arbor acre strain (70.63±1.79%).…”
Section: Effect Of Strain On Carcass Characteristics Of Birds Fed Exp...mentioning
confidence: 97%